2014
DOI: 10.1039/c4cy00092g
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of quinazolinones by acceptorless dehydrogenative coupling of o-aminobenzamide and alcohols by heterogeneous Pt catalysts

Abstract: HBEA supported Pt metal nanoclusters effectively catalyze direct dehydrogenative synthesis of quinazolinones from o-aminobenzamide and alcohols under promoter-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 26 publications
(36 reference statements)
0
45
0
1
Order By: Relevance
“…Further, catalyst loading from 5% to 25% was studied for the impact on product yield. It is found that 5,10,15,20 and 25 wt % loading of the catalyst give 45, 70, 76, 90, 91% yields respectively. 20 wt % of the catalyst was found to be the best catalyst loading to obtain maximum product yield.…”
Section: Catalytic Synthesis Of Quinazolinonesmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, catalyst loading from 5% to 25% was studied for the impact on product yield. It is found that 5,10,15,20 and 25 wt % loading of the catalyst give 45, 70, 76, 90, 91% yields respectively. 20 wt % of the catalyst was found to be the best catalyst loading to obtain maximum product yield.…”
Section: Catalytic Synthesis Of Quinazolinonesmentioning
confidence: 95%
“…),harsh reaction conditions, multistep synthesis, generation of stoichiometric amount of wastes, difficulty in product isolation, low product yields, non-recyclability of the catalysts and low reaction rates. [5][6][7][8][9] Mixed metal oxides (MMOs) formulate an important class of solid acid catalysts. They are decorated with multiple type of active sites and exhibit variable physico chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous properties of quinazolinones, developing an efficient and simple synthetic method for these compounds has been a challenge, A common strategy for the synthesis of quinazolinone derivatives is the reaction of aldehydes with aminobenzoic acid, such as 2‐aminobenzamide,, 2‐aminobenzonitrile and 2‐aminobenzoic acid . Another strategy is the reactions between 2‐aminobenzamide and primary alcohols in the presence of Pt and Pd catalysts. In addition, 2‐halobenzamides, and 2‐haloanilines have been used to synthesize quinazolinones.…”
Section: Introductionmentioning
confidence: 99%
“…A similar oxidative condensation of primary alcohols with 2-aminobenzamide to generate quinazolinones was promoted by TBHP alone [ 22 ] and together with iodine and dimethyl sulfoxide [ 23 , 24 ]. Numerous metals such as manganese [ 25 ], iron [ 26 ], nickel [ 27 ], zinc [ 28 ], ruthenium [ 29 ], iridium [ 30 ], and platinum [ 31 ] in conjunction with TBHP were also reported to promote this reaction. The option of using primary alcohols for this transformation dramatically increased the scope of the synthesis due to the vast array of available substrates.…”
Section: Introductionmentioning
confidence: 99%